Dora and the stuck truck - Beinstein, Phoebe; Roper, Robert (London : Simon and Schuster/Nicelodeon, 2008)
Dora and Boots help get the ice-cream truck unstuck from the mud with the help of Ten-Wheeler, Giant Crane, and Bulldozer.
"Based on the TV series Dora the explorer as seen on Nick Jr.".
1.0
K-3
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Trucks -- Juvenile fiction; Vehicles -- Juvenile fiction; Dora the Explorer (Fictitious character) -- Fiction; Trucks -- Fiction; Vehicles -- Fiction; Dora the Explorer (Fictional character) -- Fiction; Trucks -- Fiction; Vehicles -- Fiction